Perbandingan Jus Buah Naga dan Jambu Biji dalam Meningkatkan Kadar Hemoglobin Ibu Hamil Trimester III dengan Anemia Di Wilayah Kerja Puskesmas Krian Kabupaten Sidoarjo: Comparison of Dragon Fruit and Guava Juice in Increasing Hemoglobin Levels in Pregnant Women Trimester III with Anemia in The Region Krian Puskesmas Work Sidoarjo District - Nadiya Fatimah Perdana; Bima Suryantara; Fatimah Sari (Journal of Health, 2023)
Iron deficiency is one of the causes of anemia Pregnant women. One of the fruits that is high in iron, namely dragon fruit and fruit that is high in vitamin C, is guava fruit. This of course can increase hemoglobin levels. The purpose of this study was to determine the comparison of dragon fruit and guava juice in increasing hemoglobin levels of third trimester pregnant women with anemia in the Working Area of the Krian Health Center, Sidoarjo Regency in 2022. The method used was Quasy Experimental Two Group Pretest Posttest Design, the population is all TM III pregnant women who have anemia as many as 49 people. taken by purposive sampling as many as 44 people with inclusion criteria for third trimester pregnant women with Hb levels <11 g%, third trimester pregnant women willing to consume 100 ml of dragon fruit and guava juice regularly every day for 14 days. the results of the study it can be seen that the mean knowledge of the dragon fruit juice group was 2.68 and that of the guava juice group was 2.56. Based on the Independent T Test it was found that there was a significant difference between the two groups, this can be seen from the significance level of 0.693 (p <0.05). The conclusion is that dragon fruit juice is only slightly more effective in increasing hemoglobin levels compared to guava juice in third trimester pregnant women with anemia in the working area of the Krian Health Center, Sidoarjo Regency.